Unexpected cyclic stress-strain response of dual-phase high-entropy alloys induced by partial reversibility of deformation. (15th January 2018) - Niendorf, Thomas; Wegener, Thomas; Li, Zhiming; Raabe, Dierk
Abstract: The recently developed dual-phase high-entropy alloys are characterized by pronounced strain hardening and high ductility under monotonic loading owing to the associated transformation induced plasticity effect. Fatigue properties of high-entropy alloys have not been studied in depth so far. The current study focuses on the low-cycle fatigue regime. Cyclic tests were conducted and the microstructure evolution was studied post-mortem. Despite deformation-induced martensitic transformation during cycling at given plastic strain amplitudes, intense strain hardening in the cyclic stress-strain response is not observed. This behavior is attributed to the planar nature of slip and partial reversibility of deformation. Graphical abstract: Image 1